Book Reviews. Issue 2 (1st September 2021) - Unknown
Abstract : Frédéric Keck. Avian Reservoirs: Virus Hunters and Birdwatchers in Chinese Sentinel Posts . Durham, NC: Duke University Press, pp. 245. 2020. Lars Højer and Morten Axel Pedersen. Urban Hunters: Dealing and Dreaming in Times of Transition . New Haven, CT: Yale University Press, pp. 270. 2019.